2011
DOI: 10.1002/app.34186
|View full text |Cite
|
Sign up to set email alerts
|

Design of an ammonium dinitramide compatible polymer matrix

Abstract: To enable future environmentally friendly access to space by means of solid rocket propulsion a viable replacement to the toxic ammonium perchlorate (AP) oxidizer is needed. Ammonium dinitramide (ADN) holds great promise as a green replacement. Unfortunately compatibility issues with many polymer binder systems have hampered the development of ADN-based formulations. Herein we present proof-of-concept of a polymer cure system based on hyperbranched copolymers of 3-ethyl-3-(hydroxymethyl)oxetane (TMPO) and tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Cationic ring‐opening polymerization (CROP) is not only one of the important methods for synthesis of hyperbranched polymers, but also the key step for preparation GAPs . Hyperbranched 3‐ethyl‐3‐(hydroxymethyl)oxetane polymer obtained using CROP has been investigated as a curing agent or additive to improve the compatibility with energetic oxidants or low‐temperature properties in solid propellant systems. Furthermore, the hyperbranched polyether has been functionalized by alkyne and then made to crosslink with linear GAPs .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cationic ring‐opening polymerization (CROP) is not only one of the important methods for synthesis of hyperbranched polymers, but also the key step for preparation GAPs . Hyperbranched 3‐ethyl‐3‐(hydroxymethyl)oxetane polymer obtained using CROP has been investigated as a curing agent or additive to improve the compatibility with energetic oxidants or low‐temperature properties in solid propellant systems. Furthermore, the hyperbranched polyether has been functionalized by alkyne and then made to crosslink with linear GAPs .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbranched 3‐ethyl‐3‐(hydroxymethyl)oxetane polymer obtained using CROP has been investigated as a curing agent or additive to improve the compatibility with energetic oxidants or low‐temperature properties in solid propellant systems. Furthermore, the hyperbranched polyether has been functionalized by alkyne and then made to crosslink with linear GAPs . Hence, it is an ideal candidate as a hyperbranched structure for hybridization with linear energetic materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge with this curing system is to control the number of crosslinks per GAP chain and the amount of the acetylene compounds must therefore be low in order to form a thermoset with appropriate mechanical properties [93]. Eldsäter et al developed alkyne-functional hybrid dendritic-linear polyethers that showed excellent compatibility with ADN, and rapid curing with GAP was demonstrated through 1,3-dipolar cycloaddition [94]. Different acetylenic compounds have been used to cure GAP.…”
Section: Poly(glycidyl Azide)mentioning
confidence: 99%